Agriculture, commerce et régionalisme en Asie du Sud - DeRosa, Dean A.; Govindan, Kumaresan (International Food Policy Research Institute, 1995)
Like many other regional groups, the member countries of the South Asian Association for Regional Cooperation (SAARC)--Bangladesh , Bhutan, India, Maldives, Nepal, Pakistan, and Sri Lanka--have taken steps toward forming a regional free trade area. Will the SAARC Preferential Trading Arrangement (SAPTA) offer the substantial economic benefits, including food security, that South Asian leaders expect? This quantitative analysis compares the economic results of SAPTA with two other trade liberalization schemes, (1) more liberal trade between SAARC and the Asia-Pacific Economic Cooperation (APEC) countries, and (2) more liberal trade between SAARC and the world.